KONTRIBUSI SASTRA ANAK DALAM PEMBENTUKAN KEPRIBADIAN ANAK - Burhan Nurgiyantoro (Jurnal Cakrawala Pendidikan, 2004)
Just like adults, children, too, need various information ofthe world, ofall the things present and happening in their surroundings. To support the growth oftheir self-identity and personality, efforts should be madeto fulfil that need. Providing them with what is right fully theirs is the duty ofadults and at the same time a form oftheir appreciation ofchildren. Storytelling is one way to provide them with the information they need. Everyone likes and has.a need ofstories. Stories present and make dialogues about life in appealing and concrete ways. Through stories told, children gain the various infonnation they will need in their life.The stories intended for children's consumption can be taken from and given through children's point of view as the focus ofnarration. It is believed that children's literature contributes greatly to the development ofchildren's personality in the process ofcoming to adulthood as persons possessing clear self-identity. It is believed that literature can be a means ofimplanting, fostering, developing, and preserving values considered good and worthy by the family, society, and nation.The implantation ofvalues can be done right from the time children are still unable to speak and write will. The contribution ofchildren's literature to children's personality develop ment can be roughly differentiated into that concerning personal values and that concerning educational values, the former related to emotional and intellectual development, the development ofthe imagination, and that ofthe social, ethical, and religious senses and the latter related to the desire for exploration and discovery, to language development, to the development ofesthetic values, to multicultural insights, and to the implantation ofthe reading habit. Key words: children's literature, personality development, personal values, educational values